Produção e composição do leite de ovelhas de diferentes grupos genéticos, desempenho e terminação de cordeiros ao pé-da-mãe em pastagem cultivada - Griebler, Letieri (2012)
This study was carried out in order to evaluate the milk yield and composition from ewes of two genetic groups, as well as the influence of milk yield on performance, carcass characteristics and live weight components of nursling lambs maintained exclusively on ryegrass pasture (Lolium multiflorum LAM.). It was evaluated twelve Texel x Ile de France crossbred ewes (beef crossbred ewes) and twelve Texel (1/4) x Ile de France (1/4) x Lacaune (1/2) ewes (dairy crossbred ewes). It was included in this study only single delivered lamb and their mothers, totalizing 24 lambs from the same Sulffolk ram. The animals (ewes and lambs) were maintained throughout the experimental period in annual ryegrass in continuous grazing system with variable stocking rate. The estimation of milk yield was performed weekly. Milk samples were collected for laboratory analysis of protein, fat, density, acidity and lactose. There was a difference (P<0.05) among genotypes for milk yield (g/day), with a quadratic effect over time. Milk composition variables were not affected by treatments. The lambs were slaughtered when reaching 28 kg body weight. There was no effect (P>0.05) of the genotype of the lambs neither to the average daily weight gain nor to slaughter age. Also, there was no effect of genotype (P<0.05) on farm weight, body condition and leg length. Concerning carcass traits, only the empty body weight was affected by treatments. The gastrointestinal tract was higher (P<0.05) for lamb sons of beef crossbred ewes. Therefore, it can be inferred that the higher milk production by dairy crossbred ewes did not influence the carcass of their lambs, but induces a slower development of gastrointestinal tract of these animals comparing to lambs from the beef crossbred ewes.